Speeding Driving Behaviour: Age And Gender Experimental Analysis - S. H., Teo; Gan, Leong Ming (2015)
Road safety is a substantial issue throughout the world, this includes Malaysia. Speeding contributed to one-third of all the fatal crashes reported from year 2002 to 2011with young generation drivers reported to have the highest fatality and injury rates. This paper studied on the speeding driving behavior of 10 teenagers aged from 20 to 25, with driving experience less than 10 years and 10 adults aged from 35-40, with at least 15 years of driving experience, from both genders. The aim was to investigate the relationship between the demographic variables, which is age and gender with speeding driving behavior. In the experiment, the drivers were required to drive within an enclosed compound by using a test car. The results from the age and gender analysis respectively showed young and male drivers averagely travelled at higher velocity before entering the roundabout and at the same time accelerate to higher velocity upon exiting the roundabout compared to old and female drivers.